B isotopic constraints on the role of H2O in mantle wedge melting. (15th June 2021) - Yu, Yang; Huang, Xiao-Long; Sun, Min; Ma, Jin-Long
Abstract: The role of water on melting in the mantle wedge is still debated due to large uncertainty on the estimates of H2 O flux beneath arcs. B has been proven as an effective proxy for water flux because B and H2 O show similar chemical behaviors during subduction. The Habahe mafic dikes from the Chinese Altai were emplaced within a narrow area (<20 km from south to north) during the northward subduction of the Junggar Ocean in the middle Paleozoic. These dikes have been classified into four types with distinct geochemical and Sr-Nd-Hf-Pb isotopic compositions, which originated from mantle sources metasomatized by different subduction components, including melts from subducted sediments (Type-I, Type-IV), fluids from subducted sediments (Type-II), and melts from subducted oceanic crust (Type-III). We present B content and isotope data for the Habahe mafic dikes to investigate the influence of subduction components on melting in the mantle wedge. Type-I and -III mafic dikes all have negative δ 11 B values (−7.7‰ to −5.0‰) with variable B contents (3.65–13.4 ppm) and B/Nb ratios (2.10–7.39), indicating B isotopically light features for the subducted sediments and oceanic crust. Type-II mafic dikes have lower B contents (3.97–9.90 ppm) and higher B/Nb ratios (7.07–14.4) than Type-I mafic dikes, with a wide range of δ 11 B values from −7.8‰ to −2.7‰. This suggests that their mantle source may have been metasomatized by fluids from subducted serpentinite besides fluids from subducted sediments. Type-IV mafic dikes have higher B contents (17.0–27.5 ppm) and B/Nb ratios (25.0–40.8), and heavier B isotopic compositions (δ 11 B = −2.9‰ to +3.5‰) than Type-I mafic dikes. This indicates involvement of fluids from the slab serpentinite in metasomatism of their mantle source in addition to melts from the subducted sediments. The Habahe mafic dikes show wide range of B/Nb ratios, suggesting that different amounts of water were added into their mantle sources. These dikes exhibit variable Zr/Yb and Nb/Yb ratios, and constantly low TiO2 /Yb, indicating their formation through different degrees melting of depleted mantle sources. Their Zr/Yb and Nb/Yb ratios are negatively correlated with B/Nb, which reflects elevation of the melting degree of their mantle sources as increasing water input. Similar trends are also observed in basalts from global arcs and their major and trace elements correlate well with B/Nb ratios. Thus, water flux should play an important role on melting in the mantle wedge and control magma compositions of the arcs.